Principles and applications of soil microbiology (Prentice Hall, 2005)
Written by leading experts in their respective fields, this comprehensive, balanced introduction to soil microbiology captures the rapid advances in the study of soil microbiology—e.g., habitats and organisms, microbially mediated transformation, and applied environmental topics. Carefully edited for ease of reading, it aids users by providing an excellent multi-authored reference, the type of book that is continually used in the field. Background information is provided in the first part of the book for ease of comprehension; it then describes such fundamental topics as soil environment and microbial processes, microbial groups and their interactions, and thoroughly addresses critical nutrient cycles and important environmental and agricultural applications. An excellent desk reference and useful tool for certified professional soil scientists, environmental scientists, and others that effect environmental policy, such as soil erosion and maintenance specialists.